The Effect of Focused Group Discussion to Enhance Students’ Understanding on Premarital Sexual Behavior Risks - Daulay, Annisa Arrumaisyah; Nasution, Syawaluddin (Jurnal Kajian Bimbingan dan Konseling, 2021)
This study investigates the effectiveness of information service using a focus group discussion technique to improve students’ understanding on the risks of premarital sexual behavior. It used a quantitative experiment method with one group pretest-posttest design, while its 30 subjects were selected using purposive sampling. The data analysis process was carried out using a t-test. The research results indicate improved students’ understanding of the risks of premarital sexual behavior after they join information service with focus group discussion technique. Therefore, focus group discussion is effective to enhance students’ understanding of premarital sexual behavior risks.